NADPH Oxidase Isoforms Are Involved in Glucocorticoid-Induced Preosteoblast Apoptosis. (27th March 2019) - Bai, Shu-Cai; Xu, Qian; Li, Hui; Qin, Ya-Fei; Song, Li-Cheng; Wang, Chen-Guang; Cui, Wen-Hao; Zheng, Zhi; Yan, De-Wen; Li, Zhi-Jun; Li, Dong; Wan, Xin; et al.
Abstract : Oxidative stress induced by long-term glucocorticoid (GC) use weakens the repair capacity of bone tissue. Nicotinamide adenine dinucleotide phosphate, reduced form (NADPH) oxidase (NOX) is a superoxide-generating enzyme that plays an important role in regulating bone metabolism. To clarify the role of nonphagocytic NOX isoforms in osteoblast reactive oxygen species (ROS) generation and apoptosis, dexamethasone was used to establish a high-dose GC environment in vitro . A dose-dependent increase in intracellular ROS generation was demonstrated, which was accompanied by increased osteoblastic MC3T3-E1 cell apoptosis. Addition of the ROS inhibitor NAC ( N -acetyl-L-cysteine) or NOX inhibitor DPI (diphenyleneiodonium) reversed this effect, indicating that NOX-derived ROS can induce osteoblast apoptosis under high-dose dexamethasone stimulation. NOX1, NOX2, and NOX4 are NOX homologs recently identified in bone tissue. To clarify the NOX isoforms that play a role in osteoblast ROS generation, Nox1, Nox2, and Nox4 mRNA expression and NOX2 and NOX4 protein expression were analyzed. Nox1 and Nox4 mRNA expression was elevated in a dose-dependent manner after culture in 100 nM, 250 nM, 500 nM, or 1000 nM dexamethasone, and the increased expression of NOX1 mRNA was more significant compared with NOX4 mRNA. Small interfering RNAs (siRNAs) were used to confirm the role of NOX1 and NOX4 in ROS generation. To clarify the signaling pathway in ROS-induced osteoblast apoptosis, mitogen-activated protein kinase (MAPK) signaling molecules were analyzed. Phosphorylated ASK1 and p38 levels were significantly higher in the 1000 nM dexamethasone group, which NAC or DPI markedly attenuated. However, the total mRNA and protein levels of ASK1 and p38 between the dexamethasone group and control were not significantly different. This is related to ROS regulating the posttranslational modification of ASK1 and p38 in MC3T3-E1 cell apoptosis. Altogether, NOX1- and NOX4-derived ROS plays a pivotal role in high-dose dexamethasone-induced preosteoblast apoptosis by increasing phosphorylated ASK1 and p38 and may be an important mechanism in steroid-induced avascular necrosis of the femoral head (SANFH).